Reflections on the centenary of independence: strategic transformation of the Third Polish Republic’s defence (Economic and Political Thought, 2018)
In the strategic transformation of the Polish defence policy in the post-Cold War period, three phases can be distinguished: breaking into strategicindependence in the 1990s, integration with the Western security structuresin the first decade of the 21st century and ongoing strategic adaptation tothe neo-Cold War conditions of confrontation between Russia and the West.The transition from strategic incapacitation during the Warsaw Pact to renaissanceand the development of a full-size, creative national strategic culturebased on national interests was the main challenge in the first phase.. Themain content of the second phase was, on the one hand, the transformationof its own security system in accordance with the ever-changing conditions ofmembership in NATO and the EU, and on the other hand, gaining experiencein allied structures, including actively shaping them in accordance withPoland’s own national interests. The third phase began in 2014 in practice,when Russia’s aggression towards Ukraine and its confrontational policy ledto the formation of neo-cold war conditions of security in its relations with theWest. At the same time, the political change in Poland caused the breaking ofstrategic continuity in the functioning of the state and introduced additionalrisks to the external threats in the sphere of national security. Poland is currentlyfacing the necessity of a strategic reconstruction of national security,both in the external dimension (relations with allies) and the internal one(restoring strategic continuity in the functioning of the state).
Keywords: national security, defence, strategy, transformation, integration, NATO, Russia